(untitled) - Christian, Jeffrey M. (Hoboken, N.J., 2006)
Specific issues addressed throughout this book include: the variety of commodity investments?exchange traded funds, stocks, futures, and options; commodities in the global economy; commodity trading/investing strategies.
Keywords: Commodity exchanges,Speculation,Đầu cơ,Trao đổi hàng hóa